2004
DOI: 10.1345/aph.1d634
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clarithromycin on Inflammatory Markers in Chronic Obstructive Pulmonary Disease: Preliminary Data

Abstract: This study demonstrated that the decrease in IL-8 and TNF-alpha levels might be related to the antiinflammatory effect of clarithromycin. Thus, we suggest that the use of clarithromycin in COPD exacerbations may either treat the infection or help control the inflammation. Future studies are needed to determine the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…airway inflammation [36]. Previous studies [36,37] demonstrated that one of the anti-inflammatory mechanisms of macrolides relates to the inhibition of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…airway inflammation [36]. Previous studies [36,37] demonstrated that one of the anti-inflammatory mechanisms of macrolides relates to the inhibition of IL-8 production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their antimicrobial activity, macrolides are believed to have antiinflammatory effects, which could be especially advantageous in AECOPD. [12][13][14] In trials of chronic bronchitis, however, fluoroquinolones have been shown to reduce the risk of recurrent exacerbation when compared to macrolides. 15 The wide variation that has been observed in antibiotic selection for patients hospitalized for AECOPD suggests a high degree of uncertainty among clinicians about the benefits of different treatment options.…”
mentioning
confidence: 99%
“…Another group investigated the effects of clarithromycin on inflammatory markers in 30 men with mild to moderate COPD, who were not on corticosteroids, in a double-blind, placebo-controlled study. 60 They documented significant decreases in sputum total cell count, lL-8 and TNF levels, with similar decreases in serum inflammatory markers.…”
Section: Use Of Macrolides In Patients With Copdmentioning
confidence: 86%